Solvent effect in the synthesis of hydrophobic drug‐loaded polymer nanoparticles. Issue 4 (3rd March 2017) - Pal, Sandip; Saha, Chabita
Abstract : Quercetin is an abundant flavonoid in fruits, vegetables such as onion, tea leaves, cranberry, radish leaves etc. with numerous biological activities and widely used as an effective antioxidant. Its low solubility in water and chemical decomposition in intestinal environment are predicaments in delivery through dietary or oral intake. Noble polymeric nanoparticles are of particular interest today because of their applications in many areas. Polymer nanoparticles have attracted the interest of many research groups and have been utilised in an increasing number of fields such as site targeted drug delivery in cancer research during the last decades. Various techniques can be used to produce polymer nanoparticles, such as solvent evaporation, salting‐out, dialysis, supercritical fluid technology etc. The choice of method depends on a number of factors, such as, particle size, particle size distribution, area of application, etc. In the present study, single emulsion‐solvent evaporation technique has been utilised with two different organic solvents: acetone and chloroform/methanol to prepare quercetin loaded poly(D, L‐lactide‐co‐glycolide) nanoparticles. According to the authors' observations acetone is a better solvent for encapsulating quercetin in polymer nanoparticles owing to its physical and chemical properties.